Examining Interprofessional Collaboration across case managers, peer educators, and counselors in New York City. Issue 4 (19th May 2021) - Rahman, Rahbel; Pinto, Rogério Meireles; Troost, Jonathan P
ABSTRACT: Many individuals who are vulnerable to HIV infection and People Living with HIV (PLWH) experience fragmented prevention and care. Prevention and care service integration, pivotal for the HIV care continuum, depends on relationships among service providers and agencies offering HIV services. Case managers, counselors, and peer educators often work together to provide integrated services through interprofessional collaboration (IPC) in HIV prevention and care. Although these providers have distinct job titles, they typically offer complementary services on the HIV care continuum. To better train and allocate professional development resources for these providers, research is needed to assess the overall differences between provider-type and their demographics, intrapersonal factors, and job characteristics most likely to predict IPC engagement. We administered a cross-sectional survey to 75 counselors, 80 peer educators, and 112 case managers in 36 agencies in New York City. We performed a series of linear mixed effects models. Most of the HIV-service providers identified as Black and female and had been working for their agencies for less than a year. Knowledge and skills, self-efficacy, understanding of the community, and greater work hours (> 35 hours) were significant predictors of endorsement of IPC. Peer educators compared to case managers were more likely to reflect on the process as they provide myriad services. Eliciting perspectives from providers allows us to explore interventions, both intra-agency (trainings, greater exposure to collaborative initiatives, and supervision) and interagency (retention programs and websites promoting provider collaboration), that could facilitate IPC engagement and integrated services across the HIV care continuum.